The effect of passive heating and head cooling on perception, cardiovascular function and cognitive performance in the heat - Simmons, S. E.; Saxby, B. K.; McGlone, F. P.; Jones, D. A. (European Journal of Applied Physiology, 2008)
The present study examined the effects of raising both skin temperature and core temperature, separately and in combination, on perceptions of heat-related fatigue (alertness, contentment, calmness and thermal comfort), cardiovascular function and on objective measures of cognitive performance (reaction time and accuracy). Ten (six males) subjects had cognitive performance assessed in three conditions; at low skin and low core temperature (LL), at high skin and low core temperature (HL) and at high skin and high core temperatures (HH). In one trial, subjects had their head and neck cooled (HC); the other trial was a control (CON). Raising skin temperature increased heart rate and decreased perception of thermal comfort (P < 0.05), whereas raising both skin and core temperature decreased perception of heat-related fatigue (P < 0.05) and increased cardiovascular strain (P < 0.05) resulting in decrements in cognitive performance shown by faster reaction times (P < 0.05) and a loss of accuracy (P < 0.05). At high skin and core temperatures, cooling the head and neck improved feelings of heat-related fatigue (P < 0.05) and cardiovascular strain (P < 0.05), but had no effect on cognitive performance. In conclusion, the results of this study suggest that feelings of heat-related fatigue and cardiovascular strain can be attributed to a combination of elevated skin and core body temperature, whereas decrements in cognitive performance can be attributed to an elevated core temperature.